PENINGKATAN MINAT BELAJAR PESERTA DIDIK MELALUI PENERAPAN MODEL PROBLEM BASED LEARNING (PBL) PADA MATERI AJAR PEMISAHAN CAMPURAN DI KELAS VIII SMP NEGERI 2 WERU KABUPATEN CIREBON - Safitri, Yesi Andri; Sati, Sati; Andayana, Iwan (LPPM Politeknik Saint Paul Sorong, 2025)
This study was driven by the observation that students exhibited low interest in learning science, perceiving it as a challenging and monotonous subject. The research aimed to enhance students' interest in learning about the topic of mixture separation by utilizing the Problem-Based Learning (PBL) model, integrated with a differentiation approach and Experiential Learning in class VIII of SMP Negeri 2 Weru. This research employed a Classroom Action Research (CAR) design, implemented in two cycles, with each cycle comprising four stages: planning, implementation, observation, and reflection. The findings revealed that prior to the intervention, students' learning interest achieved only 42%, which was categorized as low. Following the intervention, students' learning interest improved to 65% in the first cycle, categorized as moderate. In the second cycle, a significant increase was recorded, with students' learning interest reaching 89%, categorized as very good. In conclusion, the application of the PBL model, supported by a differentiation approach and Experiential Learning, was effective in enhancing students' interest in learning.